Incremental water charging in agriculture. A case study of the Regione Emilia Romagna in Italy. (April 2016) - Pérez-Blanco, C.D.; Standardi, G.; Mysiak, J.; Parrado, R.; Gutiérrez-Martín, C.
Abstract: This paper explores the role that incremental water charging (temporary levies on water use) can play in reducing the environmental costs that arise during drought events. The paper combines a multi-attribute Revealed Preference Model calibrated at a local level (Agricultural District) and a regionally-calibrated Computable General Equilibrium model to estimate the impacts of incremental water charging on water use, water withdrawals and market income. The methodology is applied to the particular case of Italy's Emilia Romagna Region. Results provide a basis for the assessment of tradeoffs in water conservation. Highlights: Drought events raise relevant environmental costs. Temporary levies on water use can provide a useful tool to manage seasonal water shortages. We use a Revealed Preference Model to assess farmers' response to incremental charging. Outputs were used in a regional CGE model to estimate economy-wide implications of water charging. Results provide a basis for the assessment of tradeoffs in water conservation.